The anti-inflammatory and antioxidant effects of pigmented rice consumption in an obese cohort. Issue 12 (21st November 2019) - Callcott, Esther T.; Blanchard, Christopher L.; Snell, Peter; Santhakumar, Abishek B.
Abstract : Acute consumption of coloured rice increased antioxidant activity & reduced inflammation & lipid peroxidation biomarkers in an obese cohort. Abstract : The development of lifestyle diseases in the obese has been attributed to higher levels of inflammation and free radical mediated oxidative stress. The antioxidant and anti-inflammatory properties of polyphenols in pigmented rice varieties could have potential to neutralize oxidative stress and modulate inflammatory responses in the obese. A cross-over dietary intervention human clinical trial was conducted with three pigmented rice varieties chosen from previous chemical and in vitro antioxidant and anti-inflammatory screening. Obese ( n = 22, BMI > 30) sedentary participants consumed one cup of pigmented rice (Reiziq (brown), Purple (purple) and Yunlu29 (red)). Blood samples were collected prior consumption (baseline) and at set time points of 30 minutes, 1 hour, 2 hours and 4 hours post rice consumption. The collected blood samples were analysed for antioxidant and inflammatory biomarkers. Total antioxidant activity increased ( p < 0.001) at the 1 hour time point by 40.3% post purple rice consumption. The red rice variety, Yunlu29 increased antioxidant activity at the 30 minute ( p < 0.001) and 1 hour ( p < 0.01) time point by 29.5% and 21.2% respectively. Lipid peroxidation biomarker, malondialdehyde (MDA), decreased ( p < 0.05) at the 30 minute time point by 6.8% post purple rice consumption. At the 4 hour time point MDA levels was significantly reduced ( p < 0.001) by the red rice variety Yunlu29, by 9.6%. Pro-inflammatory cytokine, interleukin-10 (IL-10), was significantly ( p < 0.0001) reduced by 3.1% 30 minutes post purple rice consumption. In contrast, Yunlu29 (red) reduced interleukin-6 levels by 13.6% and 11.0% at the 30 minute and 1 hour time points respectively. Both the purple ( p < 0.01) and red ( p < 0.001) varieties significantly reduced interleukin-12p70 concentrations at 30 minutes by 8.7% and 10.3% respectively. Reiziq (brown) did not affect any of the biomarkers analysed in this study. The outcomes of this study highlight that polyphenols found in pigmented rice may play a key role in targeting specific therapeutic pathways in obesity-related oxidative stress and inflammation.